Estudio de la especificidad de la familia de proteínas 14-3-3 en la regulación de TAZ en células madre mesenquimales adultas - Gojanovich, Aldana Daniela (2017)
MSCs (mesenchymal stem cells) can differentiate to adipocytes and osteoblasts, among other\nmesenchymal cells. Upon activation of the Hippo pathway, the transcriptional co-regulator\nTAZ, is phosphorylated in its Ser 89, which causes its binding to 14-3-3 regulatory proteins\nin the cytoplasm. This prevents the repression of adipogenesis involved genes. In mammals,\nthe 14-3-3 family is composed of 7 paralogs that specifically bind serine or threonine\nphosphorylated residues (pS / T) in their target proteins. Our hypothesis was that the\ninteraction with TAZ was specific to one or a few 14-3-3 paralogs. Variations of the levels of these paralogs were observed during the adipogenesis of hASCs and 3T3-L1 cells. The\nvariation occurred both at mRNA and protein level, being specific for the paralogs 14-3-3y,\nB, n and E. The paralog that showed the greatest variation was 14-3-3y, wich values increased\nduring the adipogenesis of both hASCs and 3T3-L1. The results after silencing 14-3-3B\nsuggestes that this paralog could regulate the subcellular localization of TAZ. Our analysis\nsupports the current concept of specific molecular functions for the different paralogs of 14-\n3-3.